A Protection Model Against Side Effects of Cosmetic Products in E-Commerce: Perspectives from Islamic Economics, Social, and Risk Management - Adris Triseptina; Nur Ahmadi Bi Rahmani; Tri Inda Fadhila Rahma (Universitas Negeri Semarang, 2026)
This study aims to develop and conceptualize a protection model for adverse effects arising from cosmetic products purchased through e-commerce platforms by integrating Islamic economic principles, social perspectives, and risk management approaches. A qualitative research design was employed using purposive sampling to select informants who had purchased cosmetic products via e-commerce, were at least 18 years old, and had experience with product-related adverse effects or digital consumer protection mechanisms. Primary data were collected through in-depth interviews, while secondary data were obtained from platform policy documents and relevant scholarly literature. The data were analyzed using thematic analysis by linking empirical findings with the principles of maqāṣid al-sharīʿah, consumer trust, and risk management frameworks. The findings propose a comprehensive protection model consisting of preventive, responsive, and curative dimensions, encompassing product verification, claims-handling procedures, and compensation mechanisms. This model extends the literature on digital consumer protection and offers practical guidance for e-commerce platforms, regulators, and insurance providers in strengthening consumer safety and trust within the digital marketplace.